Implementation Of Cooperative Learning Model Snowball Throwing To Increase Activity And Learning Outcomes - Zaqiyaturrahmah, Eva (Classroom Action Research Journal (CARJO), 2018)
Compared to other classes, students in grade X IIS 1 majority of students have less enthusiasm or activity. After the teacher gives the materials and the students are asked to ask questions about the material that has not been understood. However, when teachers provide evaluation questions to measure students' understanding it is known that their learning outcomes are still below the predetermined KKM 75 so that some students are declared unfinished. This research uses Classroom Action Research with a qualitative approach. The data in this study was taken through observation, technical tests, documentation, and field notes. The research procedure of each cycle consists of the planning, implementation, and observation of actions and reflection actions. The results showed that the improvement of teachers' success in applying the Snowball Throwing learning model increased from the first cycle by 79.44% to 90.05%. Comparison of student activity also shows improvement from cycle I to cycle II with the average percentage of the cycle I 59,84% and become 76,08% in cycle II, so it can be concluded there is increase 15%. It can be concluded that the learning outcomes of grade X students of IIS 1 SMA Brawijaya Smart School increased by 3%.